Assessing bed shear stress effects on flow resistance of vegetated channel beds through Leaf Area Index ( LAI ) - Vittorio Pasquino; Giuseppe Francesco Cesare Lama; Cosimo Peruzzi; Giovanni Battista Chirico; Jochen Aberle (Journal of Hydrology, 2025)

Exposure to airborne particulate matter during commuting using portable sensors: Effects of transport modes in a French metropolis study case - Marie Ramel-Delobel; Cosimo Peruzzi; Thomas Coudon; Saverio De Vito; Grazia Fattoruso; Delphine Praud; Béatrice Fervers; Pietro Salizzoni (Journal of Environmental Management, 2024)

Evaluating longitudinal dispersion of scalars in rural channels of agro-urban environments - Cosimo Peruzzi; Andrea Galli; Enrico A. Chiaradia; Daniele Masseroni (Environmental Fluid Mechanics, 2021)
In agro-urban environments, the water resource conveyed by rural channels is susceptible to a gradual impoverishment due to the continuous combined sewer overflow release, constituting a pending and urgent issue for water management companies and the entire community. Reliable one-dimensional longitudinal dispersion coefficients D are required to model and study the hydrodynamics and water quality patterns at the scale of rural channel networks. Empirical formulas are usually adopted to estimate D but the accuracy in the prediction could be questionable. In order to identify which are the most suitable formulas to determine D in rural channels, field tracer measurements were carried out in three rural channels with typical geometry and configuration. The obtained D values were then compared with the most commonly used predicting formulas that the literature provides. The accuracy of the predictors was further checked by simulating different flow rates inside the tested channels by using a one-dimensional hydraulic model. Starting from the obtained results, indications and guidelines to choose the most suitable formulas to predict D in rural channels were provided. These indications should be followed when developing realistic quality models in the agro-urban environments, especially in those cases where direct measurements of the longitudinal dispersion coefficient D are not available.